A Practical Approach to Rhinoplasty. Issue 4 (April 2016) - Rohrich, Rod J.; Ahmad, Jamil
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Understand both preoperative aesthetic and functional assessment of the rhinoplasty patient. 2. Develop an operative plan to address aesthetic goals while preserving/improving nasal airway function. Summary: Rhinoplasty continues to be one of the most commonly performed aesthetic surgical procedures. Over the past 25 years, the open approach has increased in popularity and is the focus of this article. The principles for successful rhinoplasty include comprehensive clinical analysis and defining rhinoplasty goals, preoperative consultation and planning, precise operative execution, postoperative management, and critical analysis of one's results. Systematic nasal analysis is critical to establish the goals of surgery. Techniques to address the nasal dorsum, nasal airway, tip complex, alar rims, and bony vault that provide consistent results are discussed. Abstract : Related Video Content is Available Online.